Association between anthropometry and lifestyle factors and risk of B‐cell lymphoma: An exposome‐wide analysis. Issue 9 (12th November 2020) - Saberi Hosnijeh, Fatemeh; Casabonne, Delphine; Nieters, Alexandra; Solans, Marta; Naudin, Sabine; Ferrari, Pietro; Mckay, James D.; Benavente, Yolanda; Weiderpass, Elisabete; Freisling, Heinz; Severi, Gianluca; Boutron Ruault, Marie‐Christine; et al.
Abstract: To better understand the role of individual and lifestyle factors in human disease, an exposome‐wide association study was performed to investigate within a single‐study anthropometry measures and lifestyle factors previously associated with B‐cell lymphoma (BCL). Within the European Prospective Investigation into Cancer and nutrition study, 2402 incident BCL cases were diagnosed from 475 426 participants that were followed‐up on average 14 years. Standard and penalized Cox regression models as well as principal component analysis (PCA) were used to evaluate 84 exposures in relation to BCL risk. Standard and penalized Cox regression models showed a positive association between anthropometric measures and BCL and multiple myeloma/plasma cell neoplasm (MM). The penalized Cox models additionally showed the association between several exposures from categories of physical activity, smoking status, medical history, socioeconomic position, diet and BCL and/or the subtypes. PCAs confirmed the individual associations but also showed additional observations. The PC5 including anthropometry, was positively associated with BCL, diffuse large B‐cell lymphoma (DLBCL) and MM. There was a significant positive association between consumption of sugar and confectionary (PC11) and follicular lymphoma risk, and an inverse association between fish and shellfish and Vitamin D (PC15) and DLBCL risk. The PC1 including features of the Mediterranean diet and diet with lower inflammatory score showed an inverse association with BCL risk, while the PC7, including dairy, was positively associated with BCL and DLBCL risk. Physical activity (PC10) was positively associated with DLBCL risk among women. This study provided informative insights on the etiology of BCL. Abstract : What's new? The "exposome" includes all non‐genetic exposures (e.g. diet, viral, environmental, etc.), with the goal of understanding how those exposures may affect an individual's health. In this study, the authors used a technique called "EWAS" (exposome‐wide association study) to identify multiple factors that are associated with B‐cell lymphoma (BCL) risk. Their results confirm both previously reported risk factors and protective factors. In addition, they identify several previously unknown associations. These new insights, gained via the analysis of multiple exposures, suggest that traditional single‐factor approaches may be suboptimal compared with an EWAS approach.